The first experience with sodium‐glucose cotransporter 2 inhibitor for the treatment of systemic right ventricular failure. (30th March 2022) - Egorova, Anastasia D.; Nederend, Marieke; Tops, Laurens F.; Vliegen, Hubert W.; Jongbloed, Monique R.M.; Kiès, Philippine
Abstract: In congenitally corrected transposition of the great arteries, the morphological right ventricle supports the systemic circulation. This chronic exposure to pressure overload ultimately leads to systemic right ventricular (sRV) dysfunction and heart failure. Pharmacological options for the treatment of sRV failure are poorly defined and no solid recommendations are made in the most recent guidelines. Sodium‐glucose cotransporter 2 (SGLT‐2) inhibitors are a new class of antihyperglycaemic drugs that have been demonstrated to significantly reduce the risk of worsening heart failure and death from cardiovascular causes in patients with chronic heart failure with reduced left ventricular ejection fraction, yet no data are available in sRV patients. We report on the treatment and clinical follow‐up of a patient with advanced heart failure and poor sRV function in the context of congenitally corrected transposition of the great arteries, who did not tolerate sacubitril/valsartan and had a high burden of heart‐failure‐related hospitalizations. Treatment with dapagliflozin was well tolerated and resulted in (small) subjective and objective functional and echocardiographic improvement and a reduction in heart‐failure‐related hospitalizations.